1988
DOI: 10.1128/aac.32.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of cefpiramide and cefazolin into peritoneal capsular fluid in rabbits

Abstract: Penetration of cefpiramide and cefazolin into a specific extravascular fluid was measured with rabbits bearing capsules in the peritoneal cavity. A general feature of slow accumulation and elimination of drugs from extravascular sites having low surface area/volume ratios has also been observed in this study. The capsular concentration-time profiles were well expressed by the following equation: C(CF) = A(CF)[e-kel(CF)(t-to)-e-kp(CF)(t-to)], where C(CF), A(CF), kp(CF), kel(CF), and to indicate capsular concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…Various studies in animals and humans support theconcept that the protein binding of cefazolin is concentration‐dependent (saturable) within the range of concentrations likely to be encountered clinically [8, 11–14]. However these studies were conducted using human plasma in vitro [8, 11] or in animals in vivo [12–14].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in animals and humans support theconcept that the protein binding of cefazolin is concentration‐dependent (saturable) within the range of concentrations likely to be encountered clinically [8, 11–14]. However these studies were conducted using human plasma in vitro [8, 11] or in animals in vivo [12–14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with this model have demonstrated very slow elimination of cephalosporins from the capsule fluid (7,17), so it is unlikely that measuring the concentration in the capsule fluid at other times would have affected our results. Previous studies have demonstrated that cefazolin is 61.2 to 95% protein bound in rabbit serum at concentrations of 82 to 100 ,ug/ml (6,17), while cefmetazole is 53 to 59% protein bound at concentrations of 30 to 100 ,ug/ml (16,18).…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies with this model have demonstrated very slow elimination of cephalosporins from the capsule fluid (7,17), so it is unlikely that measuring the concentration in the capsule fluid at other times would have affected our results. Previous studies have demonstrated that cefazolin is 61.2 to 95% protein bound in rabbit serum at concentrations of 82 to 100 ,ug/ml (6,17), while cefmetazole is 53 to 59% protein bound at concentrations of 30 to 100 ,ug/ml (16,18). Although we did not measure protein binding in our studies, the slightly higher level of protein binding of cefazolin measured previously would have favored higher steady-state cefazolin concentrations in the infected tissue site, since it is a protein-containing extravascular site (7,8,13).…”
Section: Discussionmentioning
confidence: 47%
“…Animal studies showed cephalosporin diffusion into the disc, and many factors influence the recovery of cephazolin from tissue samples [20,27]. The factors influence the recovery of cephazolin from tissue samples, including tissue protein binding [28], the selectivity of the solid-phase cartridge and the choice of medium for homogenization. In this study, ceftazidime had highest penetration in to NP tissue, and ceftriaxone had the lowest penetration in to NP tissue.…”
Section: Discussionmentioning
confidence: 99%